Top-down network design - Oppenheimer, Priscilla (Cisco Press networking technology series, 2011)
Network designers and architects share concerns about how to design networks that can keep pace with the accelerating changes in the internetworking industry. This book covers problem areas such as traffic flow, protocol behaviours, and more.